Prediction of Cadmium Transfer From Soil to Potato in Karst Soils, China - Liu, Ke; Liu, Hongyan; Zhou, Xianyong; Chen, Zhu; Wang, Xulian (Frontiers in Environmental Science, 2021)
Contamination of food with the heavy metal Cd is a significant global concern. In this study, a field survey was performed to investigate the characteristics of Cd transfer from soil to potato tubers (n = 105). The results showed that the bioaccumulation factor of the potato tuber ranged from about 0.1 to 1. The soil threshold of Cd derived from the cumulative probability distribution was 0.15 mg kg−1 in order to protect 95% of potatoes. Additionally, prediction models for Cd transfer were constructed based on soil properties and the concentration of CaCl2-extractable soil Cd. The results of the analysis showed that pH was the critical factor affecting Cd uptake by potatoes. Additionally, the R2 of different empirical models increased from 0.354 to 0.715 as the number of soil parameters was increased, and the predicted soil Cd concentration approached the measured values at values of about 0–15 mg kg−1. The results of this study suggest that the probability distribution method was stricter than the empirical prediction models for estimating the ecological risk of Cd contamination of potatoes in karst soils.